(3ahGFO ef GdLRA GdQGHY ef cJGH GdJbQjH aj GdehGRjf GdbeQjI hGdTeSjIs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3ai PcQ ejRGf GdbeQ GdeJYdb Hadci YWGQO hGdeQjN s
(3GdfSNI HgG MhGTs
(3jdjgG fbhd ef cdGe GdMcje (B"(3HdjfGS(B" (3Yf GdajdSha SbQGW eeG ChUi Hg dJdGejPg ai cJGH GdJQGcjHs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
Keywords: (3GdcjejGA h GdWHjYjGJs